Management of Student Mental Health Programs at Zhejiang University - Li Ziwen; Karta Sasmita; Muh. Takdir (Jurnal Ilmiah Teunuleh, 2026)
In higher education, student mental health has emerged as a significant concern owing to the growing academic, social, and psychological pressures that impact students' well-being and academic performance. While numerous universities have implemented mental health services, there is still a scarcity of research focusing on the management of these programs at the institutional level, especially in top Chinese universities. This research seeks to examine the management of student mental health programs at Zhejiang University, addressing aspects such as student awareness, service accessibility, staff professionalism, program effectiveness, institutional coordination, and implementation challenges. A qualitative approach was adopted, utilizing the case study method. Data collection involved in-depth interviews, observations, document analysis, and a questionnaire distributed to 120 students. The analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. Findings reveal that the management of the student mental health program is rated highly, with an average score of 3.66. Key strengths identified include the professionalism of counsellors (4.15), service confidentiality (4.20), and service facilities (3.90). Nonetheless, challenges persist in the timeliness of services (3.32), student engagement (3.30), and stigma associated with mental health (3.75), which need to be addressed. The study's novelty lies in its thorough analysis of mental health program management from the students' perspective within a leading Chinese research university. The conclusion drawn is that Zhejiang University possesses an effective mental health management system, yet enhancements in student engagement, service coordination, program responsiveness, and stigma reduction are necessary for improved effectiveness.